2018
DOI: 10.1182/bloodadvances.2018026245
|View full text |Cite
|
Sign up to set email alerts
|

Mayo alliance prognostic system for mastocytosis: clinical and hybrid clinical-molecular models

Abstract: Systemic mastocytosis (SM) is a clinically heterogeneous disease with prognosis chiefly assigned based on World Health Organization (WHO) morphologic subclassification. We assessed the feasibility of developing contemporary risk models for SM based on clinical and integrated clinical-genetics information. Diagnosis of SM was per WHO criteria, and karyotype and next-generation sequencing data were available in a subset of the total 580 patients (median age, 55 years; range, 18-88 years) seen at the Mayo Clinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 12 publications
4
73
0
1
Order By: Relevance
“…Some recently published risk scores from our own group and from others also included variables such as anemia, thrombocytopenia, elevated alkaline phosphatase, and high molecular risk gene mutations. 10 , 22 The pivotal strengths of the current analyses include the following: indolent SM was excluded in the prognostic models because it has a nearly normal life expectancy; this analysis included the greatest number of clinically, morphologically, and genetically well-characterized patients with AdvSM ever reported; most patients had access to targeted treatment modalities such as midostaurin; and the vast majority of patients in the training set were diagnosed through fully centralized pathology and genetic analyses. An addition strength was the homogenous mutation profile (clinical and outcome characteristics) of the training set and the large and independent validation set (derived from centers with expertise in mastocytosis), particularly regarding the individual frequency of gene mutations in the S/A/R panel.…”
Section: Discussionmentioning
confidence: 99%
“…Some recently published risk scores from our own group and from others also included variables such as anemia, thrombocytopenia, elevated alkaline phosphatase, and high molecular risk gene mutations. 10 , 22 The pivotal strengths of the current analyses include the following: indolent SM was excluded in the prognostic models because it has a nearly normal life expectancy; this analysis included the greatest number of clinically, morphologically, and genetically well-characterized patients with AdvSM ever reported; most patients had access to targeted treatment modalities such as midostaurin; and the vast majority of patients in the training set were diagnosed through fully centralized pathology and genetic analyses. An addition strength was the homogenous mutation profile (clinical and outcome characteristics) of the training set and the large and independent validation set (derived from centers with expertise in mastocytosis), particularly regarding the individual frequency of gene mutations in the S/A/R panel.…”
Section: Discussionmentioning
confidence: 99%
“…Further, one study showed inferior clinical outcomes (ie, response rates, survival and disease progression) in advanced SM patients receiving midostaurin treatment, for those harboring poor‐risk mutations as compared to those without such mutations . In a recent study, two complementary risk models for SM were developed, referred to as the Mayo Alliance Prognostic System (MAPS) for SM; one model (clinical) was based on clinical variables alone while the other (hybrid clinical‐molecular) included adverse mutations as an independent risk factor . The study included 580 patients, of which 291 had indolent/smoldering SM (ISM/SSM), and 289 had “advanced” SM (100 SM‐AHN, 85 ASM and 5 MCL).…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Several attempts have been made to improve prognostication of mastocytosis by establishing scoring systems. 13,20,21 However, currently available scores are based on a limited number of patients and have not been validated in independent cohorts. More importantly, current scoring systems do not address the point that non-advanced mastocytosis and advanced systemic mastocytosis are completely different disease groups with divergent disease biology and distinct patterns of prognostic factors.…”
Section: Introductionmentioning
confidence: 99%